Mexican cinema and migration: the lost steps in The gol - den dream from Quemada-Díez - Pugibet, Veronique (Universidad de Chile. Instituto de la Comunicación e Imagen, 2017)
The cinema that cultivates violence has adopted nowadays new forms, getting to dreadful extremes as can be seen in Mexican cinema. Quemada-Díez in his mix film genre La jaula de oro, offers a specific representation of a multi faceted violence, based on real migrants’ cases confronted to disasters of social and collective order with individual consequences, as the porosity of borderlines, criminal bands, betrayals, kidnappings, rapes. Victims of an initial symbolic violence (Bourdieu), they risk their own life to obtain what the State doesn’t provide them. We have analyzed how step by step the long initiatory odyssey of some four young migrants from Guatemala and Mexico towards the North, their “American Dream”, their golden dream, turns into a genuine nightmare because of so much violence.